Book review: Datafication, governance and algorithmic power: unthinking artificial intelligences from Latin America - Ronald Sáenz Leandro (Revista CIDOB d'Afers Internacionals)
Review of the book: Danesi, Cecilia. El imperio de los algoritmos: IA inclusiva, ética y al servicio de la humanidad. Editorial Galerna, 2022, 278 págs.